Assessment of genomic and antifungal properties of Lactococcus garvieae ZB15 isolated from Zhenba bacon - Li, Guojin; He, Xingyu; Li, Jiao; Jian, Yuwen; Zhu, Lianxu; Wang, Shanshan; Zeng, Wenxian; Zhang, Tao; Lu, Hongzhao; Wang, Ling (Frontiers in Microbiology, 2025)
IntroductionLactic acid bacteria (LAB) have attracted significant interest as natural antimicrobials for food safety and preservation. Some LAB strains effectively inhibit food-borne molds and yeasts responsible for spoilage and mycotoxin contamination. However, the antifungal effect of Lactococcus garvieae remains largely unexplored.MethodsThis study investigates the properties of L. garvieae ZB15 isolated from Zhenba bacon, emphasizing its genetic safety and antimicrobial potential. The genomic information and antifungal properties of Lactococcus garvieae strain ZB15 were comprehensively analyzed using whole-genome sequencing and in vitro experiments.ResultsGenomic analysis confirmed the absence of virulence and antibiotic resistance genes, along with minimal prophage presence, underscoring its safety for application. The strain exhibited strong self-aggregation, co-aggregation, and hydrophobic properties, suggesting its potential for intestinal adhesion. The cell-free supernatant (CFS) of L. garvieae ZB15 demonstrated notable antifungal activity, achieving over 50% inhibition against four fungal strains at 60 mg/mL. The antifungal compounds in the CFS retained high activity after thermal treatment at 100°C for 1 hour, highlighting their thermal stability. Additionally, enzymatic treatments with trypsin, pepsin, and proteinase K, along with neutralization of organic acids, significantly reduced the antifungal activity, indicating the involvement of proteinaceous compounds and organic acids. Catalase treatment partially affected antifungal activity, suggesting hydrogen peroxide as a contributing factor.DiscussionLactococcus garvieae ZB15 possessed probiotic characteristics, including strong adhesion properties and pathogen exclusion capabilities. The strain’s genetic safety, lack of antibiotic resistance genes, and ability to produce heat-stable antifungal compounds highlighted its potential as a natural food preservative.